Pengembangan Kultur Sekolah Berbasis Syariah dalam Pembentukan Karakter Siswa di SMK IT Smart Informatika Surakarta - Nur Hidayah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2016)
Objective of this study is to determine development of sharia-based school culture in creating character education of students in The Integrated Islamic Vocational School (SMK IT) of Surakarta which includes factors inhibiting development of school culture and the Sharia-based solution.This study is a qualitative descriptive one. The research was conducted at SMK IT. Subjects of this study is principal, student andvice principal of student affairsof the school, while teacher, homeroom, teacher of guidance and counseling, boardinghouse caregiver as an informant. Methods of data collection used interview, observation and documentation. The results showed that the sharia-based school culture that has been developed through religious activities and school culture coming from moral values of Islam can lead to character education in everyday life, in practice there were some obstacles derived from both internal and external of the school. Internal barriers were innate character of students, lack of infrastructure, unstable team work, educational background of the student, and wicked nature of the student. As for the external factors were obstacles derived from negative impact of globalization and technological sophistication, lack of support from parents, social influence, influence of social patterns before staying at the boardinghouse. Keywords: School Culture, Sharia Culture Development, Character Education